ENGLISH GUIDE TRAINING AT GEMBA RAYA VILLAGE, KELAM PERMAI DISTRICT, SINTANG REGENCY - Ferdinanda Itu Meo; Yokie Prasetya Dharma; Henry Elisa (Jurnal Pengabdian Masyarakat Khatulistiwa, 2026)
This community service program aims to strengthen the eco-tourism potential of Betang Ensaid Panjang by improving the English communication skills of local youths and cultural practitioners in Gemba Raya Village, Kelam Regency. Although the village possesses rich Dayak Desa cultural assets and strong community hospitality, limited English proficiency has hindered residents from effectively presenting their heritage to international visitors. To address this issue, the program provides tourism-oriented English training that emphasizes functional vocabulary, guiding expressions, cultural interpretation, and confidence-building strategies. The implementation combines classroom instruction, role-play simulations, storytelling practice, and field-based guiding activities that reflect real eco-tourism settings. The training is facilitated by lecturers supported by students. Through this approach, participants develop greater fluency, accuracy, and confidence in interacting with international tourists, enabling them to communicate cultural knowledge more effectively. The outcomes of this program are expected to enhance visitor satisfaction, expand economic opportunities, and strengthen community participation in sustainable, culturally grounded tourism development. Ultimately, the initiative contributes to positioning Gemba Raya Village as a model for community-based eco-tourism empowerment in West Kalimantan.